Diagnosing acute mastoiditis in a Pediatric Emergency Department: a retrospective review - Bertolaso, Chiara; Cammisa, Ignazio; Orsini, Nicola; Sollazzo, Michela; Sardaro, Valeria; Gatto, Antonio; Chiaretti, Antonio; Sergi, Bruno (Acta Biomedica Atenei Parmensis, 2023)
Background and aim Acute mastoiditis (AM) is a common complication of acute otitis media in children. There is currently no consensus on criteria for diagnosis. Head CT is the most frequent diagnostic tool used in the ED although the increasing awareness on the use of ionized radiations in children has questioned the use of CT imaging versus solely using clinical criteria. Our research aimed to understand if CT imaging was essential in making a diagnosis of AM. Methods We retrospectively analyzed medical records from pediatric patients who accessed our Pediatric Emergency Department (ED) between January 2014 and December 2020, with a clinical suspicion of AM. We reviewed clinical symptoms upon presentation, head CT and lab values (white blood cell count or WBC, C-Reactive Protein or CRP) when done, presence of complications and discharge diagnosis. A multilogistic regression model was specified to establish the role of clinical features and of CT in the diagnosis of AM based on 77 patients. Results Otalgia (OR= 5.01; 95% CI= 1.52-16.51), protrusion of the auricle (OR= 8.42; 95% CI= 1.37-51.64) and hyperemia (OR= 4.07; 95% CI= 1.09-15.23) of the mastoid were the symptoms strongly associated with a higher probability of AM. In addition to clinical features, the adjusted OR conferred by head CT was 3.09 (95% CI = 0.92-10.34). Conclusions Clinical signs were most likely predictive of AM in our sample when compared to Head CT. Most common symptoms were protrusion of the auricle, hyperemia or swelling behind the ear and otalgia.